Dechurched Christians in Hong Kong: A Study - Ann Gillian Chu (Religions)
Though many Christian churches exist in Hong Kong, some who claim to be Christians are not members of churches, nor do they attend a Sunday service regularly. They identify as faithful but not religious. Some might even be pursuing advanced degrees in Christian studies. Why do they not join an institutional church then? Have they experienced trauma in institutional churches, and how do they process such issues? What do they hope for spiritually? Is there something in Christianity that cannot be replaced by secular spirituality which leads them to still claim to be Christians? In this article, I explore the experiences of dechurched Hong Kong Christians through archival and qualitative study, a method that foregrounds the often contradictory, complicated lived experience of faith, and ask questions about their earnestness and commitment to Christianity outside of the institutional church. I aim to understand the theological and religious perspectives of dechurched Christians and question the role of institutional churches in Hong Kong, discussing the following: (1) mundane trauma as a cause for leaving church, (2) the tendency of contemplative believers to leave church, and (3) the fragility of religious identity. I conclude that the institutional church in Hong Kong, as it is now, needs radical reimagination.